Physical and mechanical properties investigation of oxide coatings on titanium - Ramazanova, J.M.; Zamalitdinova, M.G. (Kompleksnoe Ispolzovanie Mineralnogo Syra = Complex use of mineral resources, 2019)
This paper studies the impact of rapidly flowing impulse effect of electrolytic plasma oxidation on physical and mechanical specifications of oxide coatings through the surface modification of VT1-0 titanium alloy. The present mode allows obtaining dense coatings with high mechanical properties. The electrolytic plasma oxidation process implementation leads to a micro arc-discharge emergency in a short period through the small duration values of 250 µs anodic impulse. The achieved oxide coatings have high wearing features. Frictional testing resulted in wearing features increase in 4-15 times comparing to the sample off coating at to15 µm oxide layer thickness. Friction coefficient curves of oxide coating samples have shown no destruction of the coating to the bottom. A run-in area is recognized on the curves; sliding surfaces adapt to each other and pass to the stable friction regime. The later leads to the friction coefficient reduce and wear intensity reduction.